Does freedom of testation supersede the powers of the board of trustees to allocate a death benefit in terms of section 37C of the Pension Funds Act, 24 of 1956? - Marodi, M. L. (My University, 2015)
Section 37C of the Pension Funds Act was introduced primarily to ensure that death benefits are paid in accordance with the object of the Act and government policy. Its purpose is to make sure that the dependants of the deceased member are not left destitute upon the death of the member. In order to achieve this, the death benefits are placed under the control of the trustees who are tasked with the duty to distribute the benefits equitably among the beneficiaries. According to this section, death benefits do not form part of the deceased’s estate and as a result a beneficiary under the last will and testament of the deceased is not necessarily a beneficiary under section 37C of the Act. The board of trustees will consider a person as a beneficiary if the deceased member has nominated such a person in a valid nomination form. This section therefore overrides the deceased’s freedom of testation because the board of trustees are not bound by the deceased’s wishes as completed in the nomination form. A nomination form is one of the factors which the trustees have to consider in the exercise of their discretion to make an equitable distribution.
Thesis (LLM. (Labour Law)) -- University of Limpopo, 2015
Keywords: Pension funds; Death benefits; 344.1252068; Pension trusts -- Finance -- Law and legislation -- South Africa; Social security beneficiaries; Pensions -- Law and legislation -- South Africa